Effect of nano-iron chelate on chemical composition and antimicrobial properties of Carum copticum L. essential oil and its main Terpenes from Iran - Abdossi, V; Kazemi, M (Bangladesh Journal of Botany, 2018)
The effect of exogenous application of nano-iron chelate (100 and 200 mg/l) in early flowering stage on components of essential oils (EOs) of Carum copticum was evaluated. The EO extracted by hydrodistillation from Iranian C. copticum was characterized by means of GC/MS. The nano-iron chelate application increased γ- terpinene and thymol and decreased α-pinene, β-pinene and p-cymene concentration. The oil was also subjected to antimicrobial activity. C. copticum oil was found to inhibit Bacillus cereus and Candida albicans with the lowest MIC and MBC/MFC values. Thymol and carvacrol possessed the highest antimicrobial activity among the major components. These results clearly show the antimicrobial effects of the essential oil C. copticum.